EIB Investment Report 2020/2021 Building a smart and green Europe in the Covid-19 era - European Investment Bank (European Investment Bank, 2021)
The European Union's massive efforts to rebuild after the coronavirus pandemic present a unique opportunity to transform its economy, making it more green and digital - and ultimately more competitive. The Investment Report 2020-2021 looks at the toll the pandemic took on European firms' investment and future plans, as well as their efforts to meet the demands of climate change and the digital revolution. The report's analysis is based on a unique set of databases and data from a survey of 12 500 firms conducted in the summer of 2020, in the midst of the COVID-19 crisis. While providing a snapshot of the heavy toll the pandemic took on some forms of investment, the report also offers hope by pointing out the economic areas in which Europe remains strong, such as technologies that combine green and digital innovation.